Are Disasters Ever Natural? Insights From Two Flash Floods in Port-Louis, Mauritius - Neerunjun, Henna Helvina (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2026.